2020
DOI: 10.1007/s00148-020-00800-7
|View full text |Cite
|
Sign up to set email alerts
|

Working from home and income inequality: risks of a ‘new normal’ with COVID-19

Abstract: In the current context of the COVID-19 pandemic, working from home (WFH) became of great importance for a large share of employees since it represents the only option to both continue working and minimise the risk of virus exposure. Uncertainty about the duration of the pandemic and future contagion waves even led companies to view WFH as a 'new normal' way of working. Based on influence function regression methods, this paper explores the potential consequences in the labour income distribution related to a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
217
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(268 citation statements)
references
References 95 publications
1
217
1
4
Order By: Relevance
“…High densely populated cities within the same country have shown a grater out brake of COVID-19 than less densely populated cities ( Tira, 2020 ). However, it is important to mention the limitations of the observations presented here since the analysis were made using phew parameters that is, population, km 2 , population density, ccCOVID-19 and dCOVID-19; several other studies have shown the need to focus also on weather differences among regions ( Rashed et al, 2020 ), seasonality ( Smit et al, 2020 ; Carlson et al, 2020 ) and social parameters such as income ( Bonacini, Gallo & Scicchitano, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…High densely populated cities within the same country have shown a grater out brake of COVID-19 than less densely populated cities ( Tira, 2020 ). However, it is important to mention the limitations of the observations presented here since the analysis were made using phew parameters that is, population, km 2 , population density, ccCOVID-19 and dCOVID-19; several other studies have shown the need to focus also on weather differences among regions ( Rashed et al, 2020 ), seasonality ( Smit et al, 2020 ; Carlson et al, 2020 ) and social parameters such as income ( Bonacini, Gallo & Scicchitano, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The share of employees in the service sector did not explain much of the variation in mobility changes before the lockdown, but it became an important driver during the reopening as it became positively associated to mobility reductions. A possible explanation is that a large proportion of people working in services were either still working remotely or still not allowed to work [17]. Indeed shops, bars, restaurants and department stores were still closed on the second week of May.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have focused on work arrangements such as work from home. Examples include Bonacini et al ( 2021 ), Saltiel ( 2020 ), Okubo ( 2020 ), and Rahman ( 2020 ), which examine the types of occupations and workers that have the ability to work from home and how they have been affected by the Covid-19 pandemic in countries outside the USA. A component of our contribution is linking individual demographics to access to tele-working in the USA.…”
Section: Literature Reviewmentioning
confidence: 99%